Efficacy of tantalum rod insertion for preventing femoral head collapse in osteonecrosis in a paediatric population: a pilot study. Issue 4 (25th September 2021) - Hussaini, Muqtasid; Balakumar, Jitendra; Slattery, David
ABSTRACT: Femoral head osteonecrosis in the paediatric population is difficult to treat, with the primary goals of management being prevention of subchondral collapse and the avoidance of early total hip replacement. This study aims to describe the use of a porous tantalum rod implant to provide mechanical support in preventing femoral head collapse in a paediatric population. A retrospective chart-based analysis of patients with osteonecrosis of the hip was performed at our institution to identify those who had undergone tantalum rod insertion. A total of 10 patients (fives males and five females, median age 12.5 years, 9–18) had tantalum rods implanted between December 2013 and February 2018. One patient was excluded due to follow-up at a different institution. The radiographic degree of osteonecrosis was characterized according to the Ficat classification and the Kerboul angle. Radiographic assessment of pre- and post-operative plain films was performed. The outcome measures were Tonnis grade and percentage collapse of the femoral head. Nine patients with a mean follow-up time of 18.4 months were included in the analysis. There was no significant increase in the femoral head collapse percentage post tantalum rod insertion compared to pre-operatively ( P  = 0.63). There was a significant increase in the Tonnis grade post-operatively ( P  < 0.05), with sub-group analysis showing minimal increase in Ficat Stage 1 patients. This study is the first to examine the role of tantalum rod insertion in preventing femoral head collapse in a paediatric population, with results suggesting potential benefit in a subset of patients.